Overcoming the Challenges of Recombinant Adeno-Associated Virus Production - Moura, Filipa Alves (2022)
Gene therapy is considered one of the most encouraging areas for the development of more ef- fective long-term therapeutics. These therapies rely on the delivery of genetic material to specific cells using a vector. Among the several vectors available, recombinant Adeno-Associated Viruses (rAAV) are regarded as one of the most promising viral vectors, due to the low immunogenic response, wide cellular tropism, and potential for stable expression. Despite the variety of manufacturing processes available, most of the rAAV produced in clinical trial settings are derived from transient transfection mechanisms. These systems have low scalability and high variability, which translates into high production costs. Stable producer cell line mechanisms offer an alternative to the transient transfection mechanisms by improving scalability. However, the time needed to obtain a high titer producing clone remains one of the major drawbacks. This thesis aimed to overcome these issues by using CRISPR/Cas9 genetic screens technology. To carry out the screen, two rAAV2 stable producer cell lines were developed in parallel. A cell line based on HeLaS3 was generated (clone H32D2) by transfecting a plasmid encoding all genetic material to generate rAAV2. After adaptation to suspension culture, the H32D2 clone achieved productivities levels similar to rAAV titers reported by Pharmaceutical Industry (10 11 vg/mL). In addition to the clone H32D2, a clone based on a packaging cell line (HeLaRC32) was generated. Production conditions were optimized identifying the temperature as a critical process parameter for the clone produced. The H32D2 clone was used to optimize and perform the genetic screen. Cells were infected with Lentiviral particles encoding a genome-wide CRISPR/Cas9 knockout library. rAAV2 high producing cells and low producing cells were sorted by Flow cytometry and will be used to analyze genes and pathways that have an impact on productivity and can be considered as future targets for cell engineer- ing.